PENINGKATAN PRESTASI BELAJAR IPA MELALUI PENGGUNAAN ALAT PERAGA ELEKTROMAGNET KELAS IX.6 SMPN 1 RAMBAH KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN PELAJARAN 2011/2012 - -, Erliza (Universitas Pasir Pengaraian, 2014)
This research leave from background the importance of conducted by renewalin improvement of creativity teach of the teacher in management of process physics study in SMP N 1 Rambah as respon progressively weaken him quality of learning student. In activity of study, inappropriate items of low student performance and text, at product and him learn process. Most teachers still execute traditional study.